NEW METHODS FOR STRUCTURAL DEVELOPMENT CAUSED BY OPEN INNOVATION IN RED BIOTECHNOLOGY - Kiss, Balázs; Domonkos, Dávid; Felföldi, János (Applied Studies in Agribusiness and Commerce, 2023)
Red (pharmaceutical) biotechnology is currently one of the most innovative industries. A good example of this is the fight to develop a vaccine against the COVID-19 pandemic, or even the incredible dynamism of the development of anti-cancer drugs.Innovations always carry uncertainty within them - the authors of this article see and experience this every day during their managerial work related to R&D in the biotechnology sector. Decisions often have to be made on uncertain grounds, with incomplete information. Mapping all these anomalies and their root causes is also necessary according to what has been experienced in various organizations, but at the same time it is a very interesting and challenging task. One of the possible means of sharing and reducing the risk is the so-called Open innovation, which required innovations in the fields of technical, industrial rights protection, privacy protection, but also cooperation platforms.All this required a new organizational and structural operation from the actors. This means that technological innovation attracts and results in project innovations. We assume that organizational development and structural innovations were also achieved through these transfers. We are trying to validate this hypothesis with the help of interviews with professionals.Our thesis: the challenges arising from the special innovation of red biotech also caused and necessitated the innovation of organizational structures and the development of its organizational and structural functioning, to which open innovation gave outstanding help.